Whole-genome analysis of five Escherichia coli strains isolated from focal duodenal necrosis in laying hens reveals genetic similarities to the E. coli O25:H4 ST131 strain - Yu-Yang Tsai; Julia Ienes Lima; Sonsiray Alvarez Narvaez; Catherine M. Logue (Microbiology Spectrum)
ABSTRACT Focal duodenal necrosis (FDN) is an intestinal disease causing significant economic losses in the table-egg industry due to reduced egg production in laying hens. Its etiology and pathogenesis remain poorly understood. Between 2021 and 2023, 111 Escherichia coli isolates were collected from FDN lesions and screened for the presence of virulence genes using PCR panels. Five strains—FDN-4, FDN-9, FDN-11, FDN-24, and FDN-50—were selected for whole-genome sequencing due to their high virulence gene content. Core-genome analyses found that the five FDN E. coli belong to different phylogroups and strain types (ST), but they all share multiple complete operons involved in key pathogenic functions, including host cell adhesion and invasion, iron acquisition, motility, biofilm formation, and acid resistance. Comparative genomic analyses identified FDN-4 as the most genetically distinct strain, closely resembling EC958, an O25b:H4 ST131 uropathogenic E. coli (UPEC) commonly associated with extended-spectrum beta-lactamase production. FDN-4 and EC958 share unique chromosomal virulence genes absent in the other FDN strains, all located within genomic islands. This study provides the first complete genomic characterization of E. coli isolated from FDN lesions and highlights FDN-4 as a genetically distinct strain with similarities to O25b:H4 ST131 UPEC.IMPORTANCEThis study presents the first complete genomic characterization of Escherichia coli isolated from focal duodenal necrosis (FDN) lesions. Notably, FDN-4 is the first E. coli strain from a poultry disease (FDN) to show significant similarity to O25b:H4 ST131 strains, commonly classified as uropathogenic E. coli and often associated with extended-spectrum beta-lactamase production. However, caution is warranted when attributing direct transmission routes between poultry and humans.